Pemanfaatan Limbah Organik Kotoran Ayam dan Ampas Tahu untuk Budidaya Cacing Sutera (Tubifex sp.) sebagai Pakan Glass Eel di Desa Cidadap, Kabupaten Sukabumi - Intan Wulandari; Eddy Supriyono; Dadang Shaffruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Eel fish (Anguilla bicolor) is the leading export commodity of Indonesian fisheries. New eel fish farming activities will be developed lately. The community, especially those in KUB, are interested in developing eel segmentation cultivation. But the problem is the availability of feed for glass eels, namely silk worms. Therefore, training on silkworm cultivation is important to be held. This activity was held at KUB Sidat Mandiri, Cidadap Village in November to December. Silk worm cultivation requires media with high organic content. Media that can be used for silk worm cultivation include animal waste, which has the advantage of a crude fiber protein content of 50% of the gross weight so that it is good to be used for fertilization in silk worm culture. Silk worm cultivation for glass eel feed in Cidadap Village using tofu waste animal waste fermented into fertilizer with a multilevel container system and recirculation can increase the productivity of silk worms and can guarantee the quantity and quality, for the sustainability of glass eel cultivation.